Przestrzenne zróżnicowanie wielkopowierzchniowych sieci handlowych w województwie dolnośląskim i jego uwarunkowania - Brezdeń, Paweł; Spallek, Waldemar (Przedsiębiorczość - Edukacja, 2010)
This paper deals with the spatial diversity of modern channels of retail trade represented by large shops (such as hypermarkets, supermarkets and discount shops) in the Dolnośląskie Voivodeship. This is presented against the background of the main changes to which Polish retail trade has been subjected in recent years.Despite the dynamic growth of a large retail network in Poland, the internal trade market, especially that of the grocery market, is one of the most fragmented in Europe. This still developing market is where the processes of consolidation and creation of complex networks of large shops will take place in the near future. Changing consumer preferences in favour of modern commercial buildings, but also the investment of foreign and, increasingly, Polish capital have led to this situation.The article sets out the conditions of distribution of large retail areas in the Dolnośląskie Voivodeship, which are: population density, the concentration of population (urban areas, cities), level of socio-economic development and the proximity of the German-Polish border. It shows the position of the Dolnośląskie region alongside the rest of the country within the parameters of the research. The Dolnośląskie Voivodeship is a region with a high density of retail space. Its accessibility ratio’s value is slightly lower than in those provinces with the highest values of the index, as a result of its higher population density.